Chemoenzymatic total synthesis of potent HIV RNase H inhibitor (-)-1,3,4,5-tetragalloylapiitol - Batwal, Ramesh U.; Patel, Ramesh M.; N. P. Argade (Tetrahedron-Asymmetry, 2011)
Starting from racemic dimethyl 2-acetoxy-3-methylenesuccinate, the chemoenzymatic facile total synthesis of (-)-1,3,4,5-tetragalloylapiitol has been demonstrated via an efficient lipase catalyzed resolution followed by a DIBAL reduction-double gallyolation, osmium tetroxide dihydroxylation-double gallyolation, and reductive global O-benzyl deprotection pathway. (C) 2010 Elsevier Ltd. All rights reserved.

Chemoenzymatic collective synthesis of optically active hydroxyl(methyl)tetrahydronaphthalene-based bioactive terpenoids - Batwal, Ramesh U.; N. P. Argade (Organic & Biomolecular Chemistry, 2015)
Starting from succinic anhydride and 2-methylanisole, a chemoenzymatic collective formal/total synthesis of several optically active tetrahydronaphthalene based bioactive natural products has been presented via advanced level common precursors; the natural product and antipode (-)/(+)-aristelegone B. Regioselective benzylic oxidations, stereoselective introduction of hydroxyl groups at the alpha-position of ketone moiety in syn-orientation, efficient enzymatic resolutions with high enantiomeric purity, stereoselective reductions, samarium iodide induced deoxygenations and tandem acylation-Wittig reactions without racemization and/or eliminative aromatization were the key features. An attempted diastereo-selective synthesis of (+/-)-vallapin has also been described.

Chemoenzymatic access to (+)-artabotriol and its application in collective synthesis of (+)-grandiamide D, (-)-tulipalin B, (+)-spirathundiol, and (+)-artabotriolcaffeate - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2016)
Starting from dimethyl (+/-)-2-hydroxy-3-methylenesuccinnate chemoenzymatic collective formal/total synthesis of enantiomerically pure bioactive natural products has been described via the advanced level common precursor (+)-artabotriol. An efficient enzymatic resolution with high enantiomeric purity, selective diester to diol reduction, and requisite dehydrative coupling reactions without any racemization are the significant topographies.
Keywords: (+)-artabotriol; collective synthesis; coupling reactions; dimethyl (+/-)-2-hydroxy-3-methylenesuccinate; Enzymatic resolution; Natural products; reduction